Studies on Preparation and Photocatalytic Performance of Polythiophene/TiO2 Composite Nanoparticles - Bai, Yang; Luo, Ping-Ya; Wang, Ping-Quan; Liu, Jian-Yi; Fan, Zhou; Zhang, Guang-Dong; Qian, Zhi-Wei (Asian Journal of Chemistry, 2013)
Titanium(IV) dioxide can photocatalyze degradation of organic pollutants and has been widely used in our daily life. In order to improve its photocatalytic activity, the polythiophene/TiO2 (PTh/TiO2) composite nanoparticles were prepared by in situ chemical oxidative polymerization of thiophene onto the TiO2 particles. Structures of the PTh/TiO2 composite particles were characterized by Fourier transform infrared spectroscopy and X-ray diffraction. Phenol solution was used as the target pollutant to investigate the photocatalytic activity of the composite particles. The PTh/TiO2 composite nanoparticles can degrade phenol solution effectively under UV irradiation. Their photocatalytic activities were better than that of TiO2, 1 % PTh/TiO2 composites achieved the maximum. The PTh/TiO2 composites presented in this paper are expected to be applied in the photocatalytic areas such as degrading pollutants and water purification.